Bullying in the school context: characterization, causes and consequences (Revista Internacional de Formação de Professores, 2023)
Coping with practices of violence is a contemporary challenge, especially for schools. In this sense, this bibliographical and exploratory study, using the hypothetical-deductive method of approach, aims to characterize bullying and discuss the causes and consequences of this form of violence for the lives of children and adolescents. From the material found, it was possible to draw an overview of bullying in the school context and its repercussions on the lives of those involved. The collected data show that the experiences of bullying can cause serious harm to the victims' lives. However, the intensity of these impacts differs between people, as it depends on how the victim is faced with the situation and the help they receive from parents and teachers. For this reason, it is of paramount importance that preventive and intervention programs be developed that involve parents, school and community, in order to avoid the psychological suffering of those involved and contribute to the culture of peace.
Keywords: Bullying. School context. School violence. Culture. Social peace